1974
DOI: 10.1128/aac.5.6.547
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of R Factors From Pseudomonas aeruginosa

Abstract: Sixty strains of Pseudomonas aeruginosa were selected from our clinical stock cultures and used as donors of drug resistance to examine the presence of R factors. They were highly resistant to one or more of six drugs including tetracycline (TC), chloramphenicol (CM), streptomycin (SM), sulfanilamide (SA), carbenicillin (CPC), and kanamycin (KM). Three FP − , auxotrophic mutants of P. aeruginosa were used as recipients, which had been made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…As reported previously (Iyobe et al 1974), there are two groups of MAC distribution in P. aeruginosa strains, i.e., low and high resistance group. We selected highly resistant strains of P. aeruginosa..…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…As reported previously (Iyobe et al 1974), there are two groups of MAC distribution in P. aeruginosa strains, i.e., low and high resistance group. We selected highly resistant strains of P. aeruginosa..…”
Section: Methodsmentioning
confidence: 63%
“…It is known that R plasmids are conjugally transferable among most genera of the Enterobacteriaceae (Mitsuhashi 1971), but R plasmids in P. aeruginosa are mostly transferable among the isogenic strains of P. aeruginosa (Iyobe et al 1974). From these results, we can conclude that newborn infants were contaminated in the hospital with bacteriaincluding drug-resistant strains, whic carried at a high frequency R plasmids with resistance patterns of (TC.CM.SM.SA) or (TC.CM.SM.SA.…”
Section: Results and Commentsmentioning
confidence: 99%
“…The molecular weight of Rmsl39 PCase was found to be similar to those of PCases belonging to types I and II and different from that (46,000) (5,12,13), except in a few cases such as RP4 (20,24). It is interesting to note that there are two groups of PCases mediated by R factors in P. aeruginosa strains, types I and IV.…”
Section: Methodsmentioning
confidence: 87%
“…The introduction in clinical medicine of carbenicillin (Cb) and gentamicin (Gm), antibiotics with special antipseudomonal activity, and the emergence in Pseudomonas of resistance towards these drugs have stimulated an interest in detecting the episomal nature of these resistances (3,4,27). Such studies have revealed that R-plasmids carrying genes coding for enzymes inactivating Cb or the aminoglycosides have evolved in Pseudomonas in several parts of the world (4,8,12,18,19,22,23,25,(35)(36)(37). Most of the Pseudomonas R-plasmids either have been found in Pseudomonas isolated from wounds, after long use of these antipseudomonal drugs in topical applications, or were transferable intragenerically.…”
mentioning
confidence: 99%